Effectiveness of Health Promotion Videos in Preventing Breast Cancer - Kartika Adyani; Friska Realita; Anisa Alya Maulidina (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2023)
Background: Breast cancer is the second most common type of cancer among women worldwide. Out of a total of all types of cancer (348,809 cases), breast cancer contributed 58,256 (16.7%). Lack of information, knowledge, and awareness about breast cancer often results in adolescents not taking the initiative to engage in early detection, which is the first step in preventing breast cancer. The objective of this study is to determine the educational effectiveness of breast self-examination (BSE) using leaflets and audio-visual media on the knowledge and attitudes of female students at SMA Negeri 1 Bukateja.Method: A quasi-experimental research design was employed, utilizing consecutive sampling. The study included two research groups with a total of 64 participants. Data analysis was conducted using the Chi-square test.Results: The effectiveness of audio-visual media and leaflets in increasing knowledge and attitudes of female students about BSE was found to be statistically insignificant (p-value > 0.05). Therefore, it can be concluded that both leaflets and audio-visual media have a similar effectiveness in improving adolescent attitudes towards BSE. Future researchers should consider utilizing alternative media, such as WhatsApp, for BSE education, as previous studies have shown it to be more effective than leaflets in enhancing knowledge and attitudes among young women regarding early detection of breast cancer.